Evaluation of 111In-DOTA-F56 peptide targeting VEGFR1 for potential non-invasive gastric cancer xenografted tumor mice Micro-SPECT imaging. Issue 14 (15th July 2020) - Yu, Qian; Wang, Lixin; Ding, Jin; Yang, Zhi; Shou, Chengchao; Zhao, Chuanke; Zhu, Hua
Graphical abstract: Abstract: Non-invasive imaging of vascular endothelial growth factor receptor 1 (VEGFR1) remains a great challenge in the early diagnosis of tumors, especially in gastric cancer. Here, we designed and evaluated a novel 111 In-DOTA-F56 peptide as a radioactive analogue of F56 (peptide WHSDMEWWYLLG) to bind VEGFR1. It was obtained by radiolabeling DOTA-F56 with 111 InCl3 with 98% radiochemical purity and 1.4 ± 0.4 GBq/µmol specific activity. 111 In-DOTA-F56 was obtained by the reaction of DOTA-F56 (10 µg) with 111 InCl3 in pH 4.0 sodium acetate buffer at 85 °C for 20 min. 111 In-DOTA-F56 shows good stability in 0.01 M Phosphate Buffered Saline (PBS) and 5% Human Serum Albumin (HSA). 111 In-DOTA-F56 has a high binding affinity for human gastric cancer BGC-823 cells. Bio-distribution studies of 111 In-DOTA-F56 were performed in nude mice xenografted with human gastric cancer BGC-823 cells and the results revealed tumor uptake accumulation. A blocking dose of DOTA-F56 significantly reduced the tumor uptake of 111 In-DOTA-F56. Tumors were observed with Micro-SPECT images, and the uptake in the tumor increased with time from 4 h to 24 h. The MIP of the Micro-SPECT also showed that the excess DOTA-F56 can specifically block 111 In-DOTA-F56 in a mouse tumor model. We successfully synthesized the 111 In-DOTA-F56 VEGFR1-targeted peptide as a non-invasive molecule with fine radiochemical properties. Micro-SPECT indicates tumor uptake, which can be further blocked by excess of the F56 peptide, indicating that 111 In-DOTA-F56 peptide has potential for early detection of VEGFR1 positive gastric cancer and is worthy of further clinical investigations.